A proposal on the classification of systems tracts: application the allostratigraphy and sequence stratigraphy of the colombian basin. part 1: berriasian to hauterivian (2002)
The systems tracts produced during relative sea level change cycles are subdivided in four instead of the three originally proposed by Exxon researchers. The new systems tract is named here Regressive Systems Tract (RST) and results from recognizing strata deposited in an interval of time during which relative sea level is falling. Because of these, the strata deposited during a sea level cycle are composed of progradational (RST), low aggradational, (LST), retrogradational (TST), and high aggradational (HST). The sequence boundary (SB) is placed at the base of the RST, at the horizon (Regressive Surface, RS) where relatively fast sea level fall is initiated. The base of the Lowstand Systems Tract is the Lowstand Surface (LS) reached at lowest sea level after a prolonged interval of sea level fall, and after which sea level stays low during a given interval of time. The base of the TST continues to be the Transgressive Surface (TS), as well as the base of the HST continues to be the Maximum Flooding Surface (MFS).  This subdivision of systems tracts in distinct packages of strata with more precise boundaries has been applied to the Cretaceous succession from Colombia. The systems tracts are used not only to subdivide sequences, but also to separate allostratigraphic units that can be identified in the whole basin, by identifying notorious boundaries and different patterns of sedimentation of strata above and below. The allostratigraphic units in which the predominantly marine succession of the Cretaceous Colombian Basin has been subdivided include the Cáqueza, Villeta, and Guadalupe Allogroups. The Tithonian/Berriasian to Hauterivian Cáqueza Allogroup is subdivided into the Buenavista, Macanal, and Alto de Cáqueza Alloformations. The Barremian to Santonian Villeta Allogroup is composed of the Fómeque, Une, and Chipaque Alloformations. The Campanian and Early Maastrichtian Guadalupe Allogroup is subdivided into the Lower, Middle, and Upper Guadalupe Alloformations. These are finally capped by the Late Maastrichtian lower part of the Guaduas Alloformation. Each allostratigraphic unit is composed of several lithostratigraphic units laterally adjacent and essentially synchronous, but with different types of lithology, due to lateral facies changes within a given time interval. These lithostratigraphic units deposited during evolution of the Cretaceous Colombian Basin, including valid and formally named members, formations, and groups, are discussed and compared so that a framework of correlation and exploration can be established.